Accounting as a sustainable crafted technology for human exchange activities with nature: A defense of accounting continuity - Al-Adeem, Khalid Rasheed (Frontiers in Environmental Science, 2023)
The literature in the field of accounting establishes that accounting actively changes due to its adaptability to new roles and its fulfilling of functions that members of diverse societies have needed. While accounting is a means that has assisted humans in monitoring resources and holding delegated individuals who administer such resources accountable, it is, however, also being tested to account for human activities with nature. In practice, users of corporate reports need to be informed about the sustainability of the firms in which they invest. Inquiring about sustainability is understudied and experiences low voluntary disclosure. Since reporting on sustainability embraces financial and non-financial disclosure, this study brings to attention the enterprise concept that best fits the conceptualization of accounting at this current time, enabling the accounting profession to meet the urgent ecological, environmental, and social needs of society from reporting entities, primarily those entities whose beneficiaries are part of society. Accounting is the only tool that a business possesses to monitor its internal affairs, administer its external relations, and assess its performance. Adopting the enterprise theory enables accounting to maintain its superiority as a device that meets the emerging needs of business and society. In this regard, accounting is a sustainable profession, because it maintains its existence by assisting corporations in meeting the obligations that they owe toward members of their society and reporting the impact of their actions on members of society at large.